THE REALISM OF HISTORY, THE REALISM OF FICTION (Philological Studies, 2023)
In the theoretical conceptions of the historical novel, elaborated by Elizabeth Wesseling, Brian McHale, Viktor Zmegach, three stages are ascertained through which this genre passes (traditional or realistic, modernist and postmodernist historical novel), identified through the prism of its relationship to history/historiography and through the narrative and structural manifestations of that relationship in the novel. Starting from these theoretical premises, the aim of the paper is to interpret three Macedonian novels, seen as paradigmatic for the phase of the realist historical novel: Tole Pasha and Shakjir Vojvoda by Stale Popov and The Salonica Assassins by Jovan Boshkovski. The main focus of interpretation is placed on two levels: on the novelistic relationship to history/historiography and on the structural manifestations of the relationship between literature and history.